Molecular Identification of Elasmobranch Fin Products Traded Online Using DNA Barcoding - Chandra Trisna Pangestu; Heru Pramono; Sapto Andriyono (Journal of Marine and Coastal Science, 2026)
The trade in dried shark and ray fins results in the loss of diagnostic morphological characteristics, making visual species identification difficult, particularly in online transactions. This study aims to identify elasmobranch species in dried fin products marketed online using a DNA barcoding approach based on the cytochrome c oxidase subunit I (COI) gene. The study was a descriptive-exploratory analysis of two dried fin samples obtained from Facebook listings, namely BPKUAFB1 and BPKUAFB2. DNA was extracted from fin tissue, the COI gene was amplified using universal LCO/HCO primers, and PCR products were verified via electrophoresis prior to Sanger sequencing. The sequencing results were analyzed using BLASTN against the GenBank/NCBI database and validated by phylogenetic analysis using the Neighbor-Joining method with the Kimura 2-parameter model in MEGA 12. Both samples showed 100% query coverage and 99.84% identity to the GenBank reference sequence (NC_030215), indicating a very high match with Rhina ancylostomus. Phylogenetic analysis shows that both samples cluster in a single clade with the reference sequence for Rhina ancylostomus, thereby confirming the molecular identification results. The species Rhina ancylostomus is listed as Critically Endangered (CR) on the IUCN Red List and is included in CITES Appendix II, meaning its use and trade are regulated internationally. At the national level, based on the Ministry of Marine Affairs and Fisheries Decree No. 66 of 2025 (KKP, 2025), this species is not included among protected fish species and is not listed under either full or limited protection.